Anthropometric measurements to identify undernutrition in children with cerebral palsy. (29th March 2019) - Duran, Ibrahim; Martakis, Kyriakos; Rehberg, Mirko; Semler, Oliver; Schoenau, Eckhard
Abstract : Aim: To evaluate the diagnostic performance of anthropometric indicators to identify undernutrition in children with cerebral palsy (CP). Method: The present study was a monocentric retrospective analysis of prospectively collected data among children and adolescents with CP participating in a rehabilitation program. Undernutrition was defined as a z‐score for dual‐energy X‐ray absorptiometry (DXA) determined body fat percentage less or equal to −2.0. The cut‐off values for body mass index (BMI) of the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC), and the cut‐off values for BMI and height for age of the Robert Koch Institut (RKI) were evaluated. Results: In total, 329 children with CP (181 males, 148 females, Gross Motor Function Classification System levels I–V) were eligible for analysis. The mean age was 12 years 4 months (SD 2y 9mo). The BMI cut‐off values showed the following sensitivities and specificities: WHO, sensitivity of 0.474 (95% confidence interval [CI] 0.244–0.711), specificity of 0.897 (95% CI: 0.857–0.928); CDC, sensitivity of 0.632 (95% CI: 0.384–0.837), specificity of 0.819 (95% CI: 0.772–0.861); RKI, sensitivity of 0.789 (95% CI: 0.544–0.939), specificity of 0.732 (95% CI: 0.679–0.781); and for height for age, sensitivity of 0.263 (95% CI: 0.091–0.512), specificity of 0.668 (95% CI: 0.612–0.720). Interpretation: BMI had a high specificity but very low sensitivity in identifying undernutrition in children with CP. Z‐scores for height for age had even lower specificity and sensitivity and seemed not to be appropriate for predicting undernutrition in children with CP. What this paper adds: Body mass index (BMI) z‐scores had a high specificity but very low sensitivity in identifying undernutrition in children with cerebral palsy (CP). Height z‐scores were not appropriate for predicting undernutrition in children with CP. Undernutrition assessed by BMI was overestimated in children with CP versus when assessed by dual‐energy X‐ray absorptiometry (DXA). What this paper adds: Body mass index (BMI) z‐scores had a high specificity but very low sensitivity in identifying undernutrition in children with cerebral palsy (CP). Height z‐scores were not appropriate for predicting undernutrition in children with CP. Undernutrition assessed by BMI was overestimated in children with CP versus when assessed by dual‐energy X‐ray absorptiometry (DXA). This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Mediciones antropométricas para identificar desnutrición en niños con parálisis cerebral: Objetivo: Evaluar el rendimiento diagnóstico de los indicadores antropométricos para identificar la desnutrición en niños con parálisis cerebral (PC). Método: El presente estudio realizado en un solo centro de atención, fue un análisis retrospectivo de datos recopilados prospectivamente entre niños y adolescentes con PC que participan en un programa de rehabilitación. La desnutrición se definió como una puntuación z para la absorciometría de rayos X de energía dual (DXA), y porcentaje de grasa corporal determinado menor o igual a –2, 0. Fueron evaluados los valores de corte para el índice de masa corporal (IMC) de la Organización Mundial de la Salud (OMS) y los Centros para el Control y la Prevención de Enfermedades (CDC), y los valores de corte para el IMC y la altura para la edad del Robert Koch Institut (RKI). Resultados: En total, 329 niños con PC (181 varones, 148 mujeres, con niveles I – V del Sistema de clasificación de la función motora gruesa) fueron elegibles para el análisis. La edad media fue de 12 años 4 meses (DS 2a 9m). Los valores de corte del IMC mostraron las siguientes sensibilidades y especificidades: OMS, sensibilidad de 0, 474 (intervalo de confianza del 95% [IC] 0, 244–0, 711), especificidad de 0, 897 (IC del 95%: 0, 857–0, 928); CDC, sensibilidad de 0, 632 (IC del 95%: 0, 384 a 0, 837), especificidad de 0, 819 (IC del 95%: 0, 772 a 0, 861); RKI, sensibilidad de 0, 789 (IC 95% 0, 544‐0, 939), especificidad de 0, 732 (IC 95% 0, 679‐0, 781); y para la altura para la edad, la sensibilidad de 0, 263 (IC del 95%: 0, 091 a 0, 512), la especificidad de 0, 668 (IC del 95%: 0, 612 a 0, 720). Interpretación: El IMC tenía una alta especificidad, pero una sensibilidad muy baja para identificar la desnutrición en niños con PC. Las puntuaciones Z para la altura para la edad tenían una especificidad y sensibilidad aún más bajas y no parecían ser adecuadas para predecir la desnutrición en niños con PC. Abstract : Medidas antropométricas para identificar subnutrição em crianças com paralisia cerebral: Objetivo: Avaliar o desempenho diagnóstico de indicadores antropométricos para avaliar subnutrição em crianças com paralisia cerebral (PC). Método: O presente estudo foi uma análise monocêntrica retrospectiva de dados coletados prospectivamente entre crianças e adolescentes com PC que participavam de um programa de reabilitação. A subnutrição foi definida como um escore z para porcentagem de gordura corporal determinada por absorciometria de dupla energia de raio‐X (DXA) menor ou igual a ‐2.0. Os valores de corte para o índice de massa corporal IMC) da Organização Mundial de Saúde (OMS) e dos Centros para Controle e Prevenção de Doenças (CCPD), e os valores de corte para IMC e altura por idade do Robert Koch Institut (RKI) foram avaliados. Resultados: No total, 329 crianças com PC (181 do sexo masculino, 148 do sexo feminino, níveis do Sistema de Classificação da Função Motora Grossa I–V) foram elegíveis para análise. A média de idade foi 12 anos e 4 meses (DP 2a 9m). Os valores de corte do IMC mostraram as seguintes sensibilidades e especificidades: OMS, sensibilidade de 0, 474 (intervalo de confiança [IC] a 95% 0, 244–0, 711), especificidade de 0, 897 (IC 95% 0, 857–0, 928); CCPD, sensibilidade de 0, 632 (IC 95% 0, 384–0, 837), especifididade de 0, 819 (IC 95% 0, 772–0, 861); RKI, sensibilidade de 0, 789 (IC 95% 0, 544–0, 939), especificidade de 0, 732 (IC 95% 0, 679–0, 781); e de altura por idade, sensibilidade de 0, 263 (IC 95% 0, 091–0, 512), especificidade de 0, 668 (IC 95% 0, 612–0, 720). Interpretação: O IMC teve alta especificidade mas sensibilidade muito baixa para identificar subnutrição em crianças com PC. Os escores z para altura por idade tiveram especificidade ainda menor e não pareceram apropriados para predizer subnutrição em crianças com PC.